Implementing the Fernald Method to Improve Early Reading Skills among Students with Reading Difficulties - Dewi Yanti S; Fery Muhamad Firdaus (International Journal of Social Sciences and Humanities, 2026)
This study aimed to improve the early reading skills of students with reading difficulties through the implementation of the Fernald Method in Grade II of SDN 006 Teluk Pandan. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles, each involving planning, action, observation, and reflection. The participants were five students identified with reading difficulties. Data were collected through early reading tests, observations, interviews, and documentation, and were analyzed using descriptive quantitative and qualitative techniques supported by the Normalized Gain (N-Gain) analysis. The findings revealed that the Fernald Method effectively improved students' early reading skills across all assessed aspects. The average score for letter recognition increased from 84.0 to 95.0 (N-Gain = 0.75; high category), syllable reading from 80.8 to 87.0 (N-Gain = 0.36; moderate category), word reading from 56.0 to 75.2 (N-Gain = 0.44; moderate category), and sentence reading from 36.0 to 75.0 (N-Gain = 0.61; moderate category). All participants achieved the predetermined learning mastery by the end of Cycle II. These findings indicate that the Fernald Method is an effective alternative for improving early reading skills among students with reading difficulties in inclusive elementary schools.